Analisis Penerapan Peraturan Mahkamah Agung Nomor 1 Tahun 2024 Terhadap Anak dan Lansia yang Melakukan Tindak Pidana Ringan - Serly Rahmayati; Erna Dewi; Muhammad Farid (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Law enforcement against minor crimes committed by children and the elderly often causes public dissatisfaction because it is considered to not take into account the principles of justice and benefit. To answer this problem, the Supreme Court issued Supreme Court Regulation (Perma) Number 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice. This study raises two main problems: (1) How is Perma Number 1 of 2024 applied to children and the elderly who commit minor crimes? and (2) What are the inhibiting factors in its implementation? The purpose of the study is to analyze the implementation of the Perma and identify the obstacles faced. The methods used are normative juridical and empirical juridical, with a statutory, case, and conceptual approach. Data collection was carried out through document studies and interviews with practitioners and academics. The results of the study show that Perma Number 1 of 2024 provides space for resolving minor criminal cases in a more humane manner through restorative justice. However, its implementation still faces obstacles, including the lack of understanding of law enforcement officers, limited supporting facilities, and resistance from some communities and victims who still choose the formal legal process. In conclusion, although this Perma provides a great opportunity for peaceful resolution, its implementation requires commitment from all parties. It is recommended that there be increased training and socialization for law enforcement officers, provision of penal mediation facilities, and additional regulations to strengthen protection for children and the elderly as vulnerable groups.